Design of a Car Rental Application User Interface Using Design Thinking and Kansei Engineering Approaches - Perdana Suteja Putra; Reinanrd Dustin Oktavio; Rizqa Amelia Zunaidi (Journal of Social Research, 2025)
In the growing industry 4.0, transportation is one of the important things in the development of human life, both social, cultural, political and means of mobility. The mode of transportation that can be used in meeting operational needs is a car. Cars can carry more passengers so that reaching the destination is more effective. During the rainy season, cars are preferred because they are more flexible and not afraid of being exposed to rain. In the era of technological advances, various business fields use applications to increase their customer reach, including car rental service companies. Companies that have mobile application platforms are considered more practical and flexible by users. The purpose of this research is to design the user interface of car rental mobile apps that can be tailored to pengguna feelings and to test the usability of the car rental mobile apps user interface design. The method used is design thinking as a framework and kansei engineering to translate the emotions of application users, as well as using the system usability scale for usage testing. The results of this study based on partial component analysis obtained two user interface designs formed based on the design elements that have been made. The results of the design were tested on performance matrics and System Usability Scale (SUS). It was found that concept one was the best with an effective value of 100%, an efficient value of 34.8 seconds (scenario one) and 33.1 (scenario 2). eror value of one and with an SUS value of 90.